Weather-resistant composite titanium dioxide for chemical fibers and preparation method thereof
By embedding carboxylated chitosan-polyethylene glycol grafts on the surface of titanium dioxide and combining them with modified cellulose nanofibers, the defects of composite titanium dioxide for chemical fibers in terms of weather resistance and dispersion are achieved, and the more Good color stability and dispersion performance.
Patent Information
- Application Number
- CN202411500161.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
AI Technical Summary
The existing composite titanium dioxide for chemical fibers has defects in weather resistance and dispersion, and it is difficult to maintain stable color and physical and chemical properties in complex environments, and poor dispersion in chemical fibers leads to uneven color.
The dispersion and weather resistance of the titanium dioxide are enhanced by embedding carboxylated chitosan-polyethylene glycol grafts on the surface of the titanium dioxide and bonding with modified cellulose nanofibers.
It significantly improves the dispersion and weather resistance of titanium dioxide, prevents agglomeration, enhances resistance to ultraviolet rays and high temperatures, and extends the service life of chemical fiber products.
Smart Images

Figure CN119391207A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium dioxide, and in particular to a weather-resistant composite titanium dioxide for chemical fiber and a preparation method thereof. Background Art
[0002] As an extremely important material in modern industry, chemical fiber is widely used in many fields such as clothing, home furnishings, and industry. With the continuous improvement of people's quality of life and the continuous advancement of science and technology, the quality and performance requirements of chemical fiber products are becoming increasingly stringent. In the production process of chemical fiber, titanium dioxide is often used as a pigment, which plays a key role in improving the color and performance of chemical fiber. Today, the chemical fiber industry is developing rapidly, and people have put forward higher standards for the performance of titanium dioxide for chemical fiber, among which weather resistance and dispersibility are particularly prominent.
[0003] Weather resistance refers to the ability of titanium dioxide to maintain its color and physical and chemical properties under complex environmental conditions, such as changes in light, temperature fluctuations, and oxidative environments. In practical applications, traditional composite titanium dioxide for chemical fibers is often difficult to effectively resist the invasion of ultraviolet rays due to the limitations of its surface chemical structure. Ultraviolet rays can destroy the crystal structure of titanium dioxide and cause it to change color, which leads to the gradual fading of the color of chemical fiber products and a decrease in appearance quality. At the same time, high temperatures and oxygen in the air can easily react chemically with titanium dioxide, causing it to degrade, further weakening the performance of chemical fiber products and shortening their service life.
[0004] Dispersibility refers to the ability of titanium dioxide to be evenly distributed in the chemical fiber matrix. Good dispersibility is crucial to the performance of chemical fibers. However, the surface properties of traditional composite titanium dioxide are not compatible with the chemical fiber matrix, which makes them prone to agglomeration in the chemical fiber, which will lead to a series of problems, such as uneven color of the chemical fiber, color spots or color differences, and the transparency will also be affected and become unclear.
[0005] CN114085554B discloses a method for preparing high-gloss and high-weather-resistant titanium dioxide. The method coats the surface of titanium dioxide particles with a zirconium phosphate film layer and controls the phosphorus-aluminum ratio in the pre-coating layer to reduce the photoactivity of the titanium dioxide particles and improve the weather resistance of the product. At the same time, by adding an aluminum source and a phosphorus source to the primary titanium dioxide slurry, the pre-coating layer is used as a dispersant to improve the dispersibility of the titanium dioxide. However, this method also has certain limitations. Excessive coating may increase the mutual attraction between particles, thereby affecting the dispersibility.
[0006] CN116656154A discloses a method for preparing a highly dispersible titanium dioxide, which forms a colloidal liquid in ethanol with sodium chloride to encapsulate titanium dioxide and utilizes the difference in solubility of ascorbic acid to react and remove the hydroxyl radicals on the surface of titanium dioxide in the system, so that titanium dioxide has good homogeneous dispersibility, and can still be maintained after ultraviolet light, effectively solving the problem of titanium dioxide agglomeration and improving its dispersion performance in application. However, ascorbic acid is chemically unstable, and chemical reactions such as oxidation will occur during long-term storage or use, causing hydroxyl radicals to trigger titanium dioxide photochemical reactions, causing the crystal structure to be damaged and weather resistance to decrease. In addition, ascorbic acid is mainly combined with the surface of titanium dioxide based on its elimination effect on hydroxyl radicals, but this combination lacks the strong stability of chemical bonding, and is easily separated under long-term exposure, making the hydroxyl radicals on the surface of titanium dioxide active again, further affecting weather resistance.
[0007] In summary, the existing composite titanium dioxide for chemical fiber has many shortcomings in terms of weather resistance and dispersibility, which seriously restrict the quality and application scope of chemical fiber products. Therefore, how to effectively improve the weather resistance and dispersibility of composite titanium dioxide for chemical fiber has become a key technical problem that needs to be solved urgently in the chemical fiber industry. Summary of the invention
[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing weather-resistant composite titanium dioxide for chemical fiber.
[0009] A method for preparing weather-resistant composite titanium dioxide for chemical fiber comprises the following steps:
[0010] S1. Disperse 3.5-4 parts of carboxylated chitosan in water by weight, stir, adjust the pH value of the system to 10-11, add 2.5-3 parts of polyethylene glycol, stir in a constant temperature water bath, add 10-12 parts of titanium dioxide, stir in a constant temperature water bath, cool, centrifuge, filter, and dry to obtain embedded titanium dioxide;
[0011] S2, dispersing 4-4.5 parts of cellulose nanofibers in water, ultrasonicating, adding 2.5-3 parts of citric acid, stirring in a constant temperature water bath, adding 3-3.5 parts of gluconolactone, stirring in a constant temperature water bath, cooling, centrifuging, filtering, and drying to obtain modified cellulose nanofibers;
[0012] S3, mixing the embedded titanium dioxide and the modified cellulose nanofibers, stirring in a constant temperature water bath, cooling, centrifuging, filtering, and drying to obtain a weather-resistant composite titanium dioxide for chemical fiber.
[0013] Preferably, in step S1, after the carboxylated chitosan is dispersed in water, it is stirred for 0.5-1 h at a stirring speed of 300-400 r / min.
[0014] Preferably, in step S1, after adding polyethylene glycol, stirring is performed in a constant temperature water bath, the water bath temperature is 75-80° C., the stirring time is 5-6 h, and the stirring speed is 400-500 r / min.
[0015] Preferably, in step S1, after adding titanium dioxide, stirring is performed in a constant temperature water bath, the water bath temperature is 85-90° C., the stirring time is 5-6 h, and the stirring speed is 600-700 r / min.
[0016] Preferably, in step S1, a sodium hydroxide solution with a concentration of 2-4 mol / L is used to adjust the pH value of the system to 10-11.
[0017] Preferably, in step S1, the drying time is 8-10 hours and the drying temperature is 60-65°C.
[0018] Preferably, in step S1, polyethylene glycol is added at a rate of 2-3% per minute based on the total weight of the polyethylene glycol.
[0019] Preferably, in step S2, the ultrasonic treatment is performed for 30-40 min, and the ultrasonic frequency is 40-50 kHz.
[0020] Preferably, in step S2, after adding citric acid, stirring is performed in a constant temperature water bath, the water bath temperature is 45-50° C., the stirring time is 3-4 h, and the stirring speed is 300-400 r / min.
[0021] Preferably, in step S2, the drying time is 12-14 hours and the drying temperature is 55-60°C.
[0022] Preferably, in step S2, after adding gluconolactone, stirring is performed in a constant temperature water bath, the water bath temperature is 65-70° C., the stirring time is 3-4 h, and the stirring speed is 400-500 r / min.
[0023] Preferably, in step S3, after the embedded titanium dioxide and the modified cellulose nanofibers are mixed, they are stirred in a constant temperature water bath, the water bath temperature is 75-79° C., the stirring time is 3-4 h, and the stirring speed is 300-400 r / min.
[0024] Preferably, in step S3, the drying time is 9-10 hours and the drying temperature is 55-60°C.
[0025] A weather-resistant composite titanium dioxide for chemical fiber is prepared by the preparation method of the weather-resistant composite titanium dioxide for chemical fiber according to any one of claims 1 to 9.
[0026] Beneficial effects:
[0027] In the present invention, in an alkaline environment, carboxylated chitosan and polyethylene glycol undergo a dehydration condensation reaction to obtain a structurally stable graft, whose surface carboxyl groups and amino groups react with the hydroxyl groups on the surface of titanium dioxide, which not only effectively prevents the agglomeration of titanium dioxide during use and significantly improves the dispersibility of titanium dioxide, but also forms a tight and uniform embedding layer on the surface of titanium dioxide, thereby improving the weather resistance of titanium dioxide.
[0028] Cellulose nanofibers themselves have high thermal stability, and the combination with titanium dioxide enhances the stability of the overall material at high temperatures, preventing titanium dioxide from losing its performance due to thermal decomposition, but the combination of the two is poor. In the present invention, cellulose nanofibers are combined with gluconolactone through the action of citric acid, and a large number of active functional groups are introduced on the surface of cellulose nanofibers, which can form hydrogen bonds and ester bonds with the hydroxyl and carboxyl groups on the surface of embedded titanium dioxide. On the one hand, the mutual binding force between the modified cellulose nanofibers and the embedded titanium dioxide is enhanced, so that the steric hindrance between the titanium dioxide particles is increased, the agglomeration phenomenon is effectively reduced, and the dispersibility of titanium dioxide in chemical fibers is improved; on the other hand, a relatively stable structural system is formed, which can well buffer external energy (such as ultraviolet rays, oxidation, etc.) and limit the molecular movement of titanium dioxide at high temperatures, reduce the damage to the surface structure of titanium dioxide in harsh environments, and further improve the weather resistance of titanium dioxide.
[0029] In the present invention, first, carboxylated chitosan-polyethylene glycol grafts are embedded in titanium dioxide through ester bonds and hydrogen bonds; then, cellulose nanofibers are modified to introduce more active functional groups such as carboxyl groups and hydroxyl groups; finally, the modified cellulose nanofibers and embedded titanium dioxide are combined together through a variety of chemical bonding reactions, thereby jointly improving the weather resistance and dispersibility of titanium dioxide for chemical fiber. At the same time, the preparation method is simple, the material cost is low, and it is suitable for large-scale promotion and production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a comparison chart of the color difference test of the composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2.
[0031] Figure 2 This is a comparison chart of the gloss retention rate test of the composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2.
[0032] Figure 3 This is a comparison chart of the decolorizing power test of the composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2.
[0033] Figure 4 This is a comparison chart of the mass change rate of the composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2 in an oxidizing environment.
[0034] Figure 5This is a comparison chart of the mass change rate of the composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2 in an acidic environment.
[0035] Figure 6 This is a comparison chart of the mass change rate of the composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2 in an alkaline environment. DETAILED DESCRIPTION
[0036] The present invention will be further explained below in conjunction with specific embodiments.
[0037] All the following cellulose nanofibers were purchased from Northern Century (Jiangsu) Cellulose Materials Co., Ltd., model Solid content ≥ 2%; carboxylated chitosan was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., with a carboxylation degree of 55%.
[0038] Example 1
[0039] A method for preparing weather-resistant composite titanium dioxide for chemical fiber comprises the following steps:
[0040] S1. Disperse 35g of carboxylated chitosan in 120g of water, stir for 0.5h at a stirring speed of 300r / min, adjust the pH value of the system to 10 with a sodium hydroxide solution having a concentration of 2mol / L, add 25g of polyethylene glycol, and add the polyethylene glycol at a rate of 2% per minute based on the total weight of the polyethylene glycol, stir in a constant temperature water bath at 75°C for 5h at a stirring speed of 400r / min, add 100g of titanium dioxide, stir in a constant temperature water bath at 85°C for 5h at a stirring speed of 600r / min, cool, centrifuge, filter, and dry at 60°C for 8h to obtain embedded titanium dioxide;
[0041] S2, disperse 40g of cellulose nanofibers in 500g of water, ultrasonically treat for 30min, the ultrasonic frequency is 40kHz, add 25g of citric acid, stir in a constant temperature water bath at 45℃ for 3h, the stirring speed is 300r / min, add 30g of gluconolactone, stir in a constant temperature water bath at 65℃ for 3h, the stirring speed is 400r / min, cool, centrifuge, filter, and dry at 55℃ for 12h to obtain modified cellulose nanofibers;
[0042] S3. Mix the embedded titanium dioxide and modified cellulose nanofibers, stir in a constant temperature water bath at 75°C for 3 hours at a stirring speed of 300 r / min, cool, centrifuge, filter, and dry at 55°C for 9 hours to obtain weather-resistant composite titanium dioxide for chemical fiber.
[0043] Example 2
[0044] A method for preparing weather-resistant composite titanium dioxide for chemical fiber comprises the following steps:
[0045] S1. Disperse 40g of carboxylated chitosan in 150g of water, stir for 1h at a stirring speed of 400r / min, adjust the pH value of the system to 11 with a sodium hydroxide solution having a concentration of 4mol / L, add 30g of polyethylene glycol, and add the polyethylene glycol at a rate of 3% per minute based on the total weight of the polyethylene glycol, stir in a constant temperature water bath at 80°C for 6h at a stirring speed of 500r / min, add 120g of titanium dioxide, stir in a constant temperature water bath at 90°C for 6h at a stirring speed of 700r / min, cool, centrifuge, filter, and dry at 65°C for 10h to obtain embedded titanium dioxide;
[0046] S2, disperse 45g of cellulose nanofibers in 600g of water, ultrasonically treat for 40min, the ultrasonic frequency is 50kHz, add 30g of citric acid, stir in a constant temperature water bath at 50℃ for 4h, stirring speed is 400r / min, add 35g of gluconolactone, stir in a constant temperature water bath at 70℃ for 4h, stirring speed is 500r / min, cool, centrifuge, filter, and dry at 60℃ for 14h to obtain modified cellulose nanofibers;
[0047] S3. Mix the embedded titanium dioxide and modified cellulose nanofibers, stir in a constant temperature water bath at 79° C. for 4 h at a stirring speed of 400 r / min, cool, centrifuge, filter, and dry at 60° C. for 10 h to obtain weather-resistant composite titanium dioxide for chemical fiber.
[0048] Example 3
[0049] A method for preparing weather-resistant composite titanium dioxide for chemical fiber comprises the following steps:
[0050] S1. Disperse 36g of carboxylated chitosan in 130g of water, stir for 0.6h at a stirring speed of 320r / min, adjust the pH value of the system to 10.2 with a sodium hydroxide solution having a concentration of 2.5mol / L, add 26g of polyethylene glycol, and add the polyethylene glycol at a rate of 2.2% per minute based on the total weight of the polyethylene glycol, stir in a constant temperature water bath at 76°C for 5.2h at a stirring speed of 420r / min, add 105g of titanium dioxide, stir in a constant temperature water bath at 86°C for 5.2h at a stirring speed of 620r / min, cool, centrifuge, filter, and dry at 61°C for 8.5h to obtain embedded titanium dioxide;
[0051] S2, disperse 41g of cellulose nanofibers in 520g of water, ultrasonically treat for 32min, the ultrasonic frequency is 42kHz, add 26g of citric acid, stir in a constant temperature water bath at 46°C for 3.2h, the stirring speed is 320r / min, add 31g of gluconolactone, stir in a constant temperature water bath at 66°C for 3.2h, the stirring speed is 420r / min, cool, centrifuge, filter, and dry at 56°C for 12.5h to obtain modified cellulose nanofibers;
[0052] S3. Mix the embedded titanium dioxide and modified cellulose nanofibers, stir in a constant temperature water bath at 76°C for 3.2 hours at a stirring speed of 320 r / min, cool, centrifuge, filter, and dry at 56°C for 9.2 hours to obtain weather-resistant composite titanium dioxide for chemical fiber.
[0053] Example 4
[0054] A method for preparing weather-resistant composite titanium dioxide for chemical fiber comprises the following steps:
[0055] S1. Disperse 39g of carboxylated chitosan in 140g of water, stir for 0.9h at a stirring speed of 380r / min, adjust the pH value of the system to 10.8 with a sodium hydroxide solution having a concentration of 3.5mol / L, add 29g of polyethylene glycol, and add the polyethylene glycol at a rate of 2.8% per minute based on the total weight of the polyethylene glycol, stir in a constant temperature water bath at 79°C for 5.8h at a stirring speed of 480r / min, add 115g of titanium dioxide, stir in a constant temperature water bath at 89°C for 5.8h at a stirring speed of 680r / min, cool, centrifuge, filter, and dry at 64°C for 9.5h to obtain embedded titanium dioxide;
[0056] S2, disperse 44g of cellulose nanofibers in 580g of water, ultrasonically treat for 38min, the ultrasonic frequency is 48kHz, add 29g of citric acid, stir in a constant temperature water bath at 49°C for 3.8h, the stirring speed is 380r / min, add 34g of gluconolactone, stir in a constant temperature water bath at 69°C for 3.8h, the stirring speed is 480r / min, cool, centrifuge, filter, and dry at 59°C for 13.5h to obtain modified cellulose nanofibers;
[0057] S3. Mix the embedded titanium dioxide and modified cellulose nanofibers, stir in a constant temperature water bath at 78°C for 3.8 hours at a stirring speed of 380 r / min, cool, centrifuge, filter, and dry at 59°C for 9.8 hours to obtain weather-resistant composite titanium dioxide for chemical fiber.
[0058] Example 5
[0059] A method for preparing weather-resistant composite titanium dioxide for chemical fiber comprises the following steps:
[0060] S1. Disperse 37g of carboxylated chitosan in 135g of water, stir for 0.7h, stirring speed is 350r / min, use 3mol / L sodium hydroxide solution to adjust the pH value of the system to 10.5, add 27g of polyethylene glycol, based on the total weight of polyethylene glycol, the polyethylene glycol addition rate is 2.5% per minute, stir in a constant temperature water bath at 77°C for 5.5h, stirring speed is 450r / min, add 110g of titanium dioxide, stir in a constant temperature water bath at 87°C for 5.5h, stirring speed is 650r / min, cool, centrifuge, filter, and dry at 62°C for 9h to obtain embedded titanium dioxide;
[0061] S2, disperse 42g of cellulose nanofibers in 550g of water, ultrasonically treat for 35min, the ultrasonic frequency is 45kHz, add 27g of citric acid, stir in a constant temperature water bath at 47°C for 3.5h, the stirring speed is 350r / min, add 32g of gluconolactone, stir in a constant temperature water bath at 67°C for 3.5h, the stirring speed is 450r / min, cool, centrifuge, filter, and dry at 57°C for 13h to obtain modified cellulose nanofibers;
[0062] S3. Mix the embedded titanium dioxide and modified cellulose nanofibers, stir in a constant temperature water bath at 77°C for 3.5 hours at a stirring speed of 350 r / min, cool, centrifuge, filter, and dry at 57°C for 9.5 hours to obtain weather-resistant composite titanium dioxide for chemical fiber.
[0063] Comparative Example 1
[0064] A method for preparing composite titanium dioxide for chemical fiber comprises the following steps:
[0065] S1. Disperse 42 g of cellulose nanofibers in 550 g of water, perform ultrasonic treatment for 35 min at an ultrasonic frequency of 45 kHz, add 27 g of citric acid, stir in a constant temperature water bath at 47 ° C for 3.5 h at a stirring speed of 350 r / min, add 32 g of gluconolactone, stir in a constant temperature water bath at 67 ° C for 3.5 h at a stirring speed of 450 r / min, cool, centrifuge, filter, and dry at 57 ° C for 13 h to obtain modified cellulose nanofibers;
[0066] S2. Mix 110 g titanium dioxide, 37 g carboxylated chitosan, 27 g polyethylene glycol and modified cellulose nanofibers, stir in a constant temperature water bath at 77°C for 3.5 h at a stirring speed of 350 r / min, cool, centrifuge, filter and dry at 57°C for 9.5 h to obtain composite titanium dioxide for chemical fiber.
[0067] Comparative Example 2
[0068] A method for preparing composite titanium dioxide for chemical fiber comprises the following steps:
[0069] S1. Disperse 37g of carboxylated chitosan in 135g of water, stir for 0.7h, stirring speed is 350r / min, use 3mol / L sodium hydroxide solution to adjust the pH value of the system to 10.5, add 27g of polyethylene glycol, based on the total weight of polyethylene glycol, the polyethylene glycol addition rate is 2.5% per minute, stir in a constant temperature water bath at 77°C for 5.5h, stirring speed is 450r / min, add 110g of titanium dioxide, stir in a constant temperature water bath at 87°C for 5.5h, stirring speed is 650r / min, cool, centrifuge, filter, and dry at 62°C for 9h to obtain embedded titanium dioxide;
[0070] S2. Mix the embedded titanium dioxide, 42 g of cellulose nanofibers, 27 g of citric acid, and 32 g of gluconolactone, stir in a constant temperature water bath at 77°C for 3.5 h at a stirring speed of 350 r / min, cool, centrifuge, filter, and dry at 57°C for 9.5 h to obtain composite titanium dioxide for chemical fiber.
[0071] Test Example 1
[0072] The composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2 was subjected to a weather resistance test based on light stability, as follows:
[0073] Color difference: 10 g of the titanium dioxide prepared in Example 5, Comparative Example 1, and Comparative Example 2 were weighed and added to an acetone solution, stirred to form a uniform titanium dioxide dispersion, 100 g of polyester fiber was added, and the mixture was blended and extruded using a twin-screw extruder. The mixture was injection molded into a standard test sample with a size of 100 mm × 100 mm × 3 mm using an injection molding machine. The sample was placed at room temperature for 24 hours to ensure that the surface of the sample was flat and smooth without obvious defects, thereby obtaining a chemical fiber material containing titanium dioxide;
[0074] Start the spectrophotometer (model: Konica Minolta CM-700d), preheat for 30 minutes, set the standard light box (model: TILO T60 (4)) to the D65 standard light source, place the sample on the measuring table in the standard light box, ensure that the sample surface is perpendicular to the measuring probe of the spectrophotometer and the distance is appropriate, use the spectrophotometer to measure the color parameters of each sample, then put the sample after the initial color measurement into the aging test box (model: Q-SUN Xe-3-HS) and start it, use the spectrophotometer to measure the color parameters of each sample after aging, and the instrument automatically analyzes the color difference data. Repeat the above experimental steps, record as group 1, group 2, and group 3.
[0075] Light retention rate: 10 g of the titanium dioxide prepared in Example 5, Comparative Example 1, and Comparative Example 2 were weighed and added to an acetone solution, stirred to form a uniform titanium dioxide dispersion, 100 g of polyester fiber was added, and the mixture was blended and extruded using a twin-screw extruder. The mixture was injection molded into a standard test sample with a size of 100 mm × 100 mm × 3 mm using an injection molding machine. The sample was placed at room temperature for 24 hours to ensure that the surface of the sample was flat and smooth without obvious defects, thereby obtaining a chemical fiber material containing titanium dioxide;
[0076] Start the gloss meter (model: BYK-gardner 4563), preheat for 30 minutes, select a 60° measurement angle, place the sample on the test platform of the gloss meter, measure the initial gloss value of each sample, and record the data. Place the sample in a xenon arc lamp aging test box (model: Q-SUN Xe-3-HS) and start it, measure the gloss value of each sample after aging, and record the data. Repeat the above experimental steps and record them as Group 1, Group 2, and Group 3.
[0077] Calculation formula:
[0078] Color-reducing power: Weigh the same mass of standard white pigment and colorless resin respectively, stir to make a standard mixture; weigh the same mass of titanium dioxide samples (Example 5, Comparative Example 1, Comparative Example 2), stir evenly with the standard mixture to obtain a test mixture. Apply the standard mixture and the test mixture evenly on white cards of the same material to ensure that the coating thickness is consistent, use a colorimeter to measure the color parameters of the standard mixture and the test mixture cards, obtain the reflectivity difference, and record the data. Repeat the above experimental steps, recorded as Group 1, Group 2, and Group 3.
[0079] Calculation formula:
[0080] Test Example 2
[0081] The composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2 was subjected to weather resistance tests based on thermal stability in an oxidative environment and an acid-base environment, as follows:
[0082] Oxidation environment: Weigh the same mass of titanium dioxide samples for chemical fiber in Example 5, Comparative Example 1, and Comparative Example 2 and put them into a crucible, and place the crucible in a tube furnace to ensure that the position is correct and can be heated evenly; connect the oxygen source and the tube furnace, and adjust the oxygen flow rate through a gas flow meter to prevent oxygen leakage; heat from room temperature to 400°C at a heating rate of 10°C / min, turn on a thermogravimetric analyzer (model: Netzsch STA 449F3) to perform thermogravimetric analysis on the sample, measure the mass change of the sample during the heating process, and record the data. Repeat the above experimental steps, and record them as Group 1, Group 2, and Group 3.
[0083] Acid-base environment: Weigh the titanium dioxide samples for chemical fiber in Example 5, Comparative Example 1 and Comparative Example 2 of the same mass, and divide each into two samples of the same mass to form a group, recorded as Group 1 and Group 2; add the three samples of Group 1 to an appropriate amount of 1 mol / L hydrochloric acid solution; add the three samples of Group 2 to an appropriate amount of 1 mol / L sodium hydroxide solution, stir, let stand, and drain; connect a nitrogen source and a tubular furnace, and adjust the nitrogen flow rate by a gas flowmeter; heat the sample from room temperature to 400°C at a heating rate of 10°C / min, turn on a thermogravimetric analyzer (model: Netzsch STA 449F3) to perform thermogravimetric analysis on the sample, measure the mass change of the sample during the heating process, and record the data.
[0084] The thermal stability of titanium dioxide in the above oxidizing environment and acid-base environment is calculated by the following formula:
[0085] In summary, various tests on the weather resistance of the titanium dioxide for chemical fiber prepared in Example 5 and Comparative Examples 1-2 were carried out based on testing the light stability and thermal stability. The specific results are as follows: Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 The results all show that the titanium dioxide for chemical fiber prepared in Example 5 shows the best weather resistance. This is because the graft composed of carboxylated chitosan and polyethylene glycol forms a tight and uniform embedding layer on the surface of titanium dioxide, and the modified cellulose nanofibers form hydrogen bonds and ester bonds by combining with the embedded titanium dioxide, forming a relatively stable structural system, which can well buffer external energy (such as ultraviolet rays, oxidation, etc.) and limit the molecular movement of titanium dioxide at high temperature, reduce the damage to the surface structure of titanium dioxide in harsh environments, and further improve the weather resistance of titanium dioxide. Therefore, the weather resistance in Example 5 is the best.
[0086] Test Example 3
[0087] The dispersibility of the composite titanium dioxide for chemical fiber obtained in Example 5 and Comparative Examples 1-2 was tested as follows:
[0088] Weigh the same mass of titanium dioxide samples for chemical fiber in Example 5, Comparative Example 1, and Comparative Example 2 and the same weight of polyester fiber raw material (model: SD500), mix them fully in the same proportion, add appropriate amount of water and polycarboxylate dispersant, stir, ultrasonically treat, filter, dry, grind the sample into powder, turn on the laser particle size analyzer (Malvern Mastersizer 3000) for testing, and record the data.
[0089] The particle size distribution results are shown in Table 1 below.
[0090] Table 1 Particle size distribution of Example 5, Comparative Example 1, and Comparative Example 2
[0091]
[0092] As shown in Table 1, the titanium dioxide for chemical fiber prepared in Example 5 shows the best dispersibility, which is because the graft composed of carboxylated chitosan and polyethylene glycol effectively prevents the titanium dioxide from agglomerating during use, significantly improving the dispersibility of the titanium dioxide. In addition, the modified cellulose nanofibers form hydrogen bonds and ester bonds with the embedded titanium dioxide, which enhances the mutual binding force between the two, increases the steric hindrance between the titanium dioxide particles, effectively reduces the agglomeration phenomenon, and further improves the dispersibility of the titanium dioxide in the chemical fiber.
[0093] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing weather-resistant composite titanium dioxide for chemical fiber, characterized in that: The steps include: S1. Disperse 3.5-4 parts of carboxylated chitosan in water by weight, stir, adjust the pH value of the system to 10-11, add 2.5-3 parts of polyethylene glycol, stir in a constant temperature water bath, add 10-12 parts of titanium dioxide, stir in a constant temperature water bath, cool, centrifuge, filter, and dry to obtain embedded titanium dioxide; S2, dispersing 4-4.5 parts of cellulose nanofibers in water, ultrasonicating, adding 2.5-3 parts of citric acid, stirring in a constant temperature water bath, adding 3-3.5 parts of gluconolactone, stirring in a constant temperature water bath, cooling, centrifuging, filtering, and drying to obtain modified cellulose nanofibers; S3, mixing the embedded titanium dioxide and the modified cellulose nanofibers, stirring in a constant temperature water bath, cooling, centrifuging, filtering, and drying to obtain a weather-resistant composite titanium dioxide for chemical fiber.
2. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S1, carboxylated chitosan is dispersed in water and stirred for 0.5-1h at a stirring speed of 300-400 r / min.
3. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S1, a sodium hydroxide solution with a concentration of 2-4 mol / L is used to adjust the pH value of the system to 10-11.
4. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S1, polyethylene glycol is added at a rate of 2-3% per minute based on the total weight of the polyethylene glycol.
5. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S1, after adding titanium dioxide, stirring is carried out in a constant temperature water bath for 5-6 hours, the water bath temperature is 85-90° C., and the stirring speed is 600-700 r / min.
6. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S2, ultrasonic treatment is performed for 30-40 min, and the ultrasonic frequency is 40-50 kHz.
7. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S2, after adding citric acid, stirring is carried out in a constant temperature water bath for 3-4 hours, the water bath temperature is 45-50° C., and the stirring speed is 300-400 r / min.
8. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S2, after adding gluconolactone, stirring is carried out in a constant temperature water bath for 3-4 hours, the water bath temperature is 65-70° C., and the stirring speed is 400-500 r / min.
9. The method for preparing the weather-resistant composite titanium dioxide for chemical fiber according to claim 1, characterized in that: In step S3, the drying time is 9-10 hours and the drying temperature is 55-60°C.
10. A weather-resistant composite titanium dioxide for chemical fiber, characterized in that: The weather-resistant composite titanium dioxide for chemical fiber is prepared by the preparation method of any one of claims 1 to 9.
